Diversity and antimicrobial activities of mangrove actinomycetes isolated from Tanjung Lumpur, Kuantan - Abdul Malek, Nurfathiah; Zainuddin, Zarina; Chowdhury, Ahmed Jalal Khan; Zainal Abidin, Zaima Azira (2015)
Actinomycetes represent a ubiquitous group of microorganisms that are widely distributed in nature. They are biotechnologically important for their unrivalled capacity to produce bioactive secondary metabolites. Although thousands of antibiotics have been discovered from actinomycetes, these represent only a small fraction of the entire reservoir. Thus, screening of actinomycetes from poorly studied environment is a valuable endeavour. In the present study, an effort was made to isolate, identify and evaluate the antimicrobial activities of actinomycetes from Tanjung Lumpur Mangrove Forest of Pahang, Malaysia; which is a largely underexplored ecosystem. A total of 40 isolates have been successfully isolated from 2 sampling sites. Representative isolates were characterized using 16s rRNA gene partial sequencing and further classified into 7 genera namely known as Streptomyces, Micromonospora, Rhodococcus, Gordonia, Pseudonocardia, Mycobacterium and Actinophytocola. The antimicrobial activity of the isolates were first assessed using the cross streak method against Bacillus subtilis, Candida albicans, Escherichia coli, Serratia marcescens and Staphylococcus aureus. Twenty five isolates displayed antagonistic potential against at least one of the test organisms. Of this, 40% exhibited antibacterial activity, 24% exhibited antifungal activity and 36% displayed both. The antimicrobial activity of the crude cell-free extract of these isolates were further evaluated using the double layer agar well method, in which, three isolates notably belong to the genus Streptomyces displayed broad antimicrobial activities against all test organisms. The presence of relatively large numbers of actinomycetes with promising inhibitory activities suggest that mangrove of Tanjung Lumpur is a rich repertoire of actinomycetes having interesting bioactive secondary metabolites.